The effectiveness of using peer correction on improving writing skills to students in intensive English classes at Hanoi Law University - Lã, Nguyễn Bình Minh (ĐHNN, 2017)
This minor thesis consists of five chapters. In this chapter, the challenge as well as approaches to EFL writing is briefly discussed; scope and rational of the study stated. The purpose and organization of the study are also mentioned. Chapter two is the review of literature which attempts to put the study in a proper context. Chapter three describes method and procedure. Chapter four reports and analyzes quantitative and qualitative findings. The last chapter presents the pedagogical implications of the study and points out its limitations and suggestions for further research.